Assistant Decisionmaking Method for Gaits of Hexapods Robot Based on Fuzzy Reasoning in Complex Terrain - YOU Bo; WANG Minglei; XU Jiazhong; LI Jiayu; DING Liang; GAO Haibo (Journal of Harbin University of Science and Technology)
The drivers of manned hexapod robots rely on subjective experience in decisionmaking in complex terrain In order to improve the quality of drivers′ decisionmaking, an auxiliary decisionmaking method is proposed The information processing model of drivers is established, and the terrain is used as the decision factor while the priorities of gaits as the result The fuzzy decisionmaking system is established to assist the drivers The slope, fluctuation, roughness and barrier height are defined as the terrain features, degrees of membership are classified and the fuzzy rules are formulated The semiphysical simulation platform of the hexapod manipulation is used to compare the decision results of the drivers with auxiliary and without auxiliary The experimental results show that the auxiliary decision method can assist the driver to make reasonable decisions when the terrain changes, and increase stability and maneuverability of the hexapod robot in complex terrain